URGENSI PENCEGAHAN PERUNDUNGAN DUNIA MAYA (CYBERBULLYING) TERHADAP PELAJAR - Rabiah Al Adawiah; Esther Masri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Cyberbullying has become a worrying phenomenon inthe last decade, especially among students. Cyberbullying is anew form of bullying that involves the use of electronic media.Difference other forms of bullying, cyberbullying reaches a muchwider audiences at great speed, transcending physical andpersonal boundaries of time and space. The impact ofcyberbullying cases is more devastating than traditionalbullying, because it leaves digital records such as photos, videos,and writings so that the memory and shame for the victim willcontinue as long as the digital footprint is accessed by people.Therefore, the importance of prevention efforts in order to avoidand not fall into the dangers and impacts of cyberbullying andthe legal aspects that govern it. Activities carried out amongstudents in the form of counseling through webinars arepreventive measures that need to be carried out by students inorder to avoid the dangers and impacts of cyberbullying as wellas legal aspects that regulate if cyberbullying occurs. Thepurpose of this activity is to increase knowledge andunderstanding of students of SMK Industri Nasional 1, SetuBekasi , in order to avoid cyberbullying, both as perpetrators andvictims.